THE RELATIONSHIP OF KNOWLEDGE ABOUT HIV/AIDS WITH PREVENTIVE BEHAVIOR IN ADOLESCENTS AT SENIOR HIGH SCHOOL 15 BEKASI CITY IN 2023 - Intan Kencanawati; Lisna Agustina; Kiki Deniati (Rena Cipta Mandiri, 2023)
HIV transmission occurs due to lack of knowledge about HIV/AIDS. Adolescent knowledge about HIV/AIDS is part of the Millennium Development Goals (MDGs) indicators, if not immediately given knowledge and understanding about HIV/AIDS, especially its treatment and prevention, it can have an impact, for example, because of ignorance adolescents often have sexual intercourse with more than one partner. The purpose of this study was to determine the relationship between knowledge about HIV/AIDS and preventive behavior among adolescents at SMAN 15 Bekasi City in 2023. This research method used a cross sectional design with simple random sampling technique and used a questionnaire through google form to 151 respondents at SMAN 15 Bekasi city. This study used the chi-square statistical test to determine the relationship of the two variables. Based on the results of the chi-square test analysis with a value of p = 0.000 (p <0.050), it was stated that H0 was rejected. So it can be interpreted that there is a relationship between knowledge about HIV/AIDS and preventive behavior among adolescents at SMAN 15 Bekasi City in 2023.